Cysteine Boosts Fitness Under Hypoxia-Mimicked Conditions in Ovarian Cancer by Metabolic Reprogramming - Nunes, Sofia C.; Ramos, Cristiano; Santos, Inês; Mendes, Cindy; Silva, Fernanda; Vicente, João B.; Pereira, Sofia A.; Félix, Ana; Gonçalves, Luís G.; Serpa, Jacinta (Frontiers in Cell and Developmental Biology, 2021)
Among gynaecologic malignancies, ovarian cancer is the third most prevalent and the most common cause of death, especially due to diagnosis at an advanced stage together with resistance to therapy. As a solid tumour grows, cancer cells in the microenvironment are exposed to regions of hypoxia, a selective pressure prompting tumour progression and chemoresistance. We have previously shown that cysteine contributes to the adaptation to this hypoxic microenvironment, but the mechanisms by which cysteine protects ovarian cancer cells from hypoxia-induced death are still to be unveiled. Herein, we hypothesized that cysteine contribution relies on cellular metabolism reprograming and energy production, being cysteine itself a metabolic source. Our results strongly supported a role of xCT symporter in energy production that requires cysteine metabolism instead of hydrogen sulphide (H2S) per se. Cysteine degradation depends on the action of the H2S-synthesizing enzymes cystathionine β-synthase (CBS), cystathionine γ-lyase (CSE) and/or 3-mercaptopyruvate sulfurtransferase (MpST; together with cysteine aminotransferase, CAT). In normoxia, CBS and CSE inhibition had a mild impact on cysteine-sustained ATP production, pointing out the relevance of CAT+MpST pathway. However, in hypoxia, the concomitant inhibition of CBS and CSE had a stronger impact on ATP synthesis, thus also supporting a role of their hydrogen sulphide and/or cysteine persulphide-synthesizing activity in this stressful condition. However, the relative contributions of each of these enzymes (CBS/CSE/MpST) on cysteine-derived ATP synthesis under hypoxia remains unclear, due to the lack of specific inhibitors. Strikingly, NMR analysis strongly supported a role of cysteine in the whole cellular metabolism rewiring under hypoxia. Additionally, the use of cysteine to supply biosynthesis and bioenergetics was reinforced, bringing cysteine to the plateau of a main carbon sources in cancer. Collectively, this work supports that sulphur and carbon metabolism reprogramming underlies the adaptation to hypoxic microenvironment promoted by cysteine in ovarian cancer.